Progress in the opto-electronic oscillator - a ten year anniversary review - Yao, X.S.; Maleki, L.; Eliyahu, D. (2004 IEEE MTT-S International Microwave Symposium, 2004)
The opto-electronic oscillator (OEO), which uses an optical energy storage element to achieve low phase noise, represents a paradigm shift for generating high quality microwave signals. Since its first demonstration of low phase noise potential ten years ago at JPL, the OEO has been steadily improving its phase noise performance, frequency stability, and robustness. Now the OEO has moved beyond the laboratory and entered into real world applications, ranging from aerospace to telecommunications to instrumentation.